Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1152/ajpregu.00043.2008
|View full text |Cite
|
Sign up to set email alerts
|

Central G-alpha subunit protein-mediated control of cardiovascular function, urine output, and vasopressin secretion in conscious Sprague-Dawley rats

Abstract: The role(s) of central Galpha-proteins in the regulation of cardiovascular and renal function is unknown. We examined how inhibition/downregulation of central Galphai/Galphao, Galphaz or Galphaq proteins altered the characteristic cardiovascular (depressor), renal excretory (diuretic), and plasma AVP (inhibitory) responses to intracerebroventricular injection of nociceptin/orphanin FQ (N/OFQ) in rats. Before investigation, rats were pretreated intracerebroventricularly with saline vehicle (5 microl, 48 h, n=6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Extending this further, in investigations performed in conscious rats, we demonstrated that the cardiovascular depressor (hypotension and bradycardia), but not diuretic, responses produced by activation of a central GPCR [the nociceptin/orphanin FQ (N/OFQ) peptide receptor] were completely abolished in rats that had been pre‐treated (48 h) centrally with Pertussis toxin (PTX). These findings highlight the novel functionally selective central Gα‐subunit protein‐mediated control of cardiovascular versus renal excretory function in vivo (Wainford et al ., 2008). However, as PTX, which was used in these studies, is an exotoxin that catalyses the ADP ribosylation of all Gα i/o subunit proteins, the specific Gα i(1–3) or Gα o subunit(s) involved in mediating central GPCR‐evoked cardiovascular depressor responses were not elucidated.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Extending this further, in investigations performed in conscious rats, we demonstrated that the cardiovascular depressor (hypotension and bradycardia), but not diuretic, responses produced by activation of a central GPCR [the nociceptin/orphanin FQ (N/OFQ) peptide receptor] were completely abolished in rats that had been pre‐treated (48 h) centrally with Pertussis toxin (PTX). These findings highlight the novel functionally selective central Gα‐subunit protein‐mediated control of cardiovascular versus renal excretory function in vivo (Wainford et al ., 2008). However, as PTX, which was used in these studies, is an exotoxin that catalyses the ADP ribosylation of all Gα i/o subunit proteins, the specific Gα i(1–3) or Gα o subunit(s) involved in mediating central GPCR‐evoked cardiovascular depressor responses were not elucidated.…”
Section: Introductionmentioning
confidence: 77%
“…in combination with xylazine (5 mg/kg, i.m.) 5–7 days before experimentation as previously described (Wainford et al ., 2008; Wainford and Kapusta, 2009; 2010). On the day of study, rats were anaesthetized with sodium methohexital (75 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to these findings, our present results strongly suggest that in high-salt-treated rats, the prolonged hypotension produced by central N/OFQ counters/masks the characteristic decrease in RSNA by a pathway that involves the baroreflex. Although RSNA can have significant impact on the renal excretion of water and sodium (16,17,20) our previous studies have shown the diuretic (and antinaturetic) response to central N/OFQ can occur via a renal nerve-independent pathway (19) involving the suppression of AVP release into the systemic circulation (15,34). This may explain why intracerebroventricular N/OFQ continued to produce a diuretic response in animals maintained on a chronic high-NaCl diet.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cardiovascular and renal responses produced by central administration of N/OFQ are well characterized, the endogenous role(s) of the N/OFQ-NOP receptor system remain unclear. Both N/OFQ and NOP receptors are highly expressed in CNS sites that regulate cardiovascular and renal homeostasis (25,34). N/OFQ has been demonstrated to play a critical modulatory role in the adaptive behavioral fear responses to stressful stimuli (5, 12); therefore it is likely that the endogenous N/OFQ-NOP receptor system plays a physiologically important role in regulating cardiovascular and renal responses to acute/chronic stressors (18).…”
mentioning
confidence: 99%